A method for efficiently preparing a diamond / copper composite
Patent Information
- Application Number
- CN202611410293.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-27
AI Technical Summary
然而,上述研究对于异种界面调控手段复杂,制备周期长,难以满足工业化需求
本发明采用盐浴镀法在金刚石表面制备铬镀层,通过调节镀覆温度对镀层厚度实现可控制备,金刚石表面镀铬后,Cr与金刚石表面的C原子反应生成碳化物,形成Cr3C2,Cr7C3等碳化物,有效改善金刚石与铜之间的界面润湿性,镀铬后的复合材料相比未镀铬的热导率显著提升。
Smart Images

Figure CN122979688A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-performance thermal conductive material preparation technology, specifically, it relates to an efficient preparation method for diamond / copper composite materials. Background Technology
[0002] In the field of high-performance integrated circuits, high thermal conductivity materials with excellent performance have become a key area for breakthroughs. Diamond / copper composite materials, with their high thermal conductivity and low coefficient of thermal expansion, have become a research hotspot for next-generation electronic packaging materials.
[0003] To address the interfacial bonding problem between diamond and copper, scholars both domestically and internationally have conducted extensive research to obtain diamond / copper composite materials with excellent properties. Li Zhijiang et al. (A diamond-copper matrix composite material and its preparation method, CN121555835 A) proposed a method for preparing diamond / copper composite materials: modified diamond powder and copper powder are ball-milled and mixed, and then hot-pressed and sintered to obtain a diamond-copper core material. After activation treatment, Ni / Pr alloy target material is magnetron sputtered onto the upper and lower surfaces of the activated diamond-copper core material to form a Ni / Pr composite intermediate layer. Finally, copper sheets are vacuum-welded onto the upper and lower surfaces of the Ni / Pr composite intermediate layer to obtain the diamond-copper matrix composite material. Ren et al. (Diamond-coated composite materials, copper composite materials and their preparation methods, CN 121295109 A) proposed depositing an amorphous carbon film on the surface of cleaned diamond particles and performing a first heat treatment to obtain amorphous carbon-coated diamond. A metal layer was then deposited on the surface of the amorphous carbon-coated diamond, followed by a second heat treatment to obtain coated diamond. A third heat treatment was then performed on the coated diamond, and subsequently, the diamond-coated composite material was prepared using a gas pressure melt infiltration method, successfully producing a uniform diamond / copper composite material with minimal damage. However, the above research involves complex methods for controlling the heterogeneous interface and has a long preparation cycle, making it difficult to meet industrial requirements. Therefore, there is an urgent need to find efficient methods for preparing diamond / copper composite materials and controlling their interfaces. Summary of the Invention
[0004] To address the problems mentioned above in the background art, this invention proposes an efficient preparation method for diamond / copper composite materials, specifically including: S1. Cleaning and surface activation pretreatment of diamond particles; S2. Chromium plating is performed on the pretreated diamond surface using a salt bath plating method to obtain diamond particles containing a chromium plating layer. S3. The diamond particles containing the chromium plating layer are mixed with copper powder and subjected to DC-assisted hot pressing sintering to obtain a diamond / copper composite sintered body. S4. The diamond / copper composite sintered body is subjected to electrical pulse treatment, and after cleaning and drying, the diamond / copper composite material is obtained.
[0005] Preferably, in step S1, during the pretreatment process, the surface is ultrasonically cleaned for 10-30 minutes each with deionized water, acetone and anhydrous ethanol, then soaked in dilute nitric acid for 30 minutes for surface activation, neutralized with sodium hydroxide solution to neutralize the acidic dirt on the surface, and then ultrasonically cleaned with deionized water.
[0006] Preferably, in step S2, during the salt bath plating process, the molar ratio of diamond particles to chromium powder is 10:1, a mixed salt of NaCl:KCl of 1:1 is used, the plating temperature is 800~900℃, the holding time is 30~90 min, and the process is carried out under argon atmosphere protection.
[0007] Preferably, in step S3, the volume ratio of the diamond particles to the copper powder is 3:7.
[0008] Preferably, in step S3, the DC-assisted heating sintering temperature is 800~950℃, the pressure is 70~90 MPa, and the holding time is 10~30 min.
[0009] Preferably, in step S4, the electrical pulse processing parameters are: voltage 40~60 V, frequency 400~500 Hz, and pulse time 1~3 min.
[0010] Preferably, the duty cycle of the electrical pulse processing is 95%~98%, and the current density is 30~40 A / cm². 2 .
[0011] Preferably, the diamond particles are MBD8 type diamond particles with a particle size of 200 μm; the chromium powder is spherical chromium powder with a particle size of 10 μm; and the copper powder is spherical copper powder with a particle size of 15~53 μm.
[0012] Preferably, during the cleaning and drying process, the sample is ultrasonically cleaned in anhydrous ethanol for 30 minutes, then removed and dried.
[0013] Compared with the prior art, the technical solution disclosed herein has the following beneficial technical effects: This invention uses a salt bath plating method to prepare a chromium plating layer on the surface of diamond. The plating temperature is adjusted to control the thickness of the plating layer. After chromium plating on the diamond surface, Cr reacts with C atoms on the diamond surface to form carbides, such as Cr3C2 and Cr7C3, which effectively improves the interfacial wettability between diamond and copper. The thermal conductivity of the composite material after chromium plating is significantly improved compared with that without chromium plating.
[0014] In the preparation of diamond / copper composite materials, this invention involves holding the temperature for 30-90 minutes in the salt bath plating stage, only 10-30 minutes in the hot pressing sintering stage, and only 1-3 minutes in the electric pulse treatment stage, significantly reducing the total process time compared to existing technologies. By combining salt bath chromium plating with DC-assisted hot pressing sintering and electric pulse treatment, high thermal conductivity, low coefficient of expansion, and high density are ensured while achieving efficient and low-cost preparation.
[0015] The above description is merely an overview of the technical solutions of the embodiments of this application. In order to better understand the technical means of the embodiments of this application and to implement them in accordance with the contents of the specification, and to make the above and other objects, features and advantages of the embodiments of this application more obvious and understandable, specific implementation methods of this application are described below. Attached Figure Description
[0016] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings of the embodiments will be briefly described below. It should be understood that the drawings described below only relate to some embodiments of this disclosure and are not intended to limit this disclosure, wherein: Figure 1 This is a flowchart of the preparation process provided by the present invention; Figure 2 This refers to the microstructure of the diamond / copper interface before the electrical pulse in Embodiment 1 of the present invention. Figure 3 This is the microstructure of the copper / molybdenum diamond / copper interface after an electrical pulse in Embodiment 1 of the present invention. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are also within the scope of protection of this disclosure.
[0018] The term "embodiment" as used herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of the phrase "embodiment" in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0019] like Figure 1 As shown, this invention provides an efficient method for preparing diamond / copper composite materials, specifically including: S1. Select MBD8 type diamond particles with a particle size of 200μm, spherical chromium powder with a particle size of 10μm, and spherical copper powder with a particle size of 15~53μm. First, ultrasonically clean the diamond particles with deionized water for 10~30 min to remove adsorbed water-soluble impurities from the surface. Then, ultrasonically clean them with acetone for 10~30 min to remove organic matter from the surface. Further, ultrasonically clean them with anhydrous ethanol solution for 10~30 min to remove excess acetone solution. Further still, surface activation is performed by soaking in dilute nitric acid for 30 min. Subsequently, acidic dirt on the surface of the diamond particles is neutralized with sodium hydroxide solution. Finally, ultrasonically clean them multiple times with deionized water to remove excess impurities. S2. Chromium plating is performed on the pretreated diamond surface using a salt bath plating method. In some embodiments of the present invention, the specific salt bath plating parameters are as follows: diamond particles and chromium powder are mixed evenly at a molar ratio of 10:1 and placed in an alumina crucible. A layer of mixed salt (NaCl:KCl=1:1) is then placed on the surface of the crucible. The crucible is placed in an atmosphere tube furnace and heated to the plating temperature under Ar atmosphere protection, preferably 800~900℃, for example, 800℃, 820℃, 850℃, 880℃, or 900℃. The holding time is preferably 30~90 min, for example, 30 min, 50 min, 70 min, or 90 min. The furnace is then cooled, and the mixture is washed with distilled water and dried to obtain diamond particles with a chromium plating layer. S3. Mix diamond particles with chromium plating with copper powder in a volume ratio of 3:7, and perform DC-assisted hot pressing sintering to obtain a diamond / copper composite sintered body. In some embodiments of the present invention, the DC-assisted hot pressing sintering process is selected such that the sintering temperature is preferably 800~950℃, for example, 800℃, 850℃, 900℃, or 950℃; the pressure is preferably 70~90 MPa, for example, 70MPa, 75MPa, 80MPa, 85MPa, or 90MPa; and the holding time is preferably 10~30 min, for example, 10 min, 15 min, 20 min, 25 min, or 30 min.
[0020] S4. The diamond / copper composite sintered body was subjected to electrical pulse treatment, ultrasonically cleaned in anhydrous ethanol for 30 min, and then dried to obtain the diamond / copper composite material.
[0021] In some embodiments of the present invention, the process parameters for the electrical pulse processing are as follows: the voltage is preferably 40~60 V, for example, 40V, 45V, 50V, 55V, or 60V; the frequency is preferably 400~500 Hz, for example, 400Hz, 420Hz, 450Hz, 480Hz, or 500Hz; and the pulse time is preferably 1~3 min, for example, 1 min, 1.5 min, 2 min, 2.5 min, or 3 min.
[0022] In some embodiments of the present invention, the specific strategy of the process steps and parameters used in the preparation of the present invention is as follows: Chromium plating on the diamond surface by salt bath plating can improve the wettability of the diamond / copper interface. At the diamond / chromium interface, various carbides such as Cr3C2 and Cr7C3 will be formed, and the types and distribution of carbides are uneven. At the same time, there will be incomplete coatings on the diamond surface, which causes the resistivity of different regions of the interface to differ, providing a physical basis for the local heating of the subsequent electrical pulse; further, the chromium-plated diamond and copper are sintered by DC-assisted hot pressing sintering, which eliminates the diamond / copper voids and utilizes the high-resistivity contact surface caused by the different material interfaces (the high-resistivity contact surface formed between the diamond, chromium plating, and copper substrate due to the difference in material resistivity, and the different carbides) The resistivity of the materials also varies, and there are voids in the incomplete coating layer, forming a gradient thermal effect from the inside out at the diamond / copper interface (when DC current passes through the sintered body, the resistivity of each component is different, and the current preferentially passes along the low-resistivity path, generating local Joule heat concentration in the high-resistivity interface region, forming a gradient temperature field from the inside out, driving the carbide to grow gradient from the diamond surface outward). This eliminates macroscopic voids, improves density, and achieves interfacial metallurgical bonding and densification of the composite material. Unlike existing technologies, this invention performs independent short-time electrical pulse treatment on the formed diamond / copper composite material after DC-assisted hot pressing sintering. Utilizing the non-uniformity of salt bath chromium plating, the resistivity of the gradient-distributed carbides varies, targeting different intermediate phases (Cr3C2, Cr7C3, Cr...). 23 By adjusting the pulse parameters (such as C6), diamond, Cr3C2, Cr7C3, and Cr are formed on the original gradient structure. 23 The C6 and copper mixed gradient transition layer allows for local current and temperature differences at the diamond / copper composite interface, regulating the formation type of the interfacial reaction layer. This promotes the transformation of carbides in locally high-resistivity regions into more stable carbides, fosters uniform distribution of the intermediate phase, and prevents overall overheating that could lead to diamond graphitization. Furthermore, by using pulsed current to generate a flow concentration effect around defects such as pores, local Joule heat healing of residual pores and other defects at the interface enables the efficient preparation of high thermal conductivity diamond / copper composite materials.
[0023] The following is an explanation with reference to specific embodiments: Example 1
[0024] A highly efficient method for preparing diamond / copper composite materials is provided, comprising the following steps: S1: Raw material preparation: Select MBD8 type diamond particles with a particle size of 200μm, spherical chromium powder with a particle size of 10μm, and spherical copper powder with a particle size of 15μm. First, ultrasonically clean the diamond particles with deionized water for 10 min to remove water-soluble impurities adsorbed on the surface. Then, ultrasonically clean them with acetone for 30 min to remove organic matter on the surface. Further, ultrasonically clean them with anhydrous ethanol solution for 10 min to remove excess acetone solution. Further still, surface activation is performed by soaking in dilute nitric acid for 30 min. Subsequently, acidic dirt on the surface of the diamond particles is neutralized with sodium hydroxide solution. Finally, ultrasonically clean them multiple times with deionized water to remove excess impurities.
[0025] S2. Chromium plating on diamond surface: Chromium plating is performed on the cleaned diamond surface using a salt bath plating method. Diamond particles and chromium powder are mixed evenly at a molar ratio of 10:1 and placed in an alumina crucible. A layer of mixed salt (NaCl:KCl=1:1) is then placed on the surface. The crucible is placed in an atmosphere tube furnace and heated to 800 ℃ under Ar atmosphere protection for 90 min. After cooling with the furnace, the diamond particles are washed with distilled water and dried to obtain the coated diamond particles.
[0026] S3. DC-assisted hot pressing sintering: Salt bath-plated diamond particles and copper powder are mixed at a volume ratio of 3:7, and then rapidly hot-pressed and sintered at a temperature of 800 ℃, a pressure of 90 MPa, and a holding time of 30 min.
[0027] S4. Electrical Pulse Treatment: The sintered diamond / copper composite material is subjected to electrical pulse treatment. The electrical pulse treatment process parameters are: voltage 40 V, frequency 500 Hz, pulse time 1 min, duty cycle 95%, and current density 40 A / cm². 2 .
[0028] S5. After electrical pulse treatment, the diamond / copper composite material is cleaned by ultrasonic cleaning in anhydrous ethanol for 30 minutes to remove surface impurities. The material is then removed and dried to obtain a high-performance diamond / copper composite material.
[0029] The interfaces of the diamond / copper composite material after DC-assisted hot pressing and sintering and after electrical pulse were observed using scanning electron microscopy in this embodiment. Figure 2 and Figure 3 As shown.
[0030] Without electrical pulse treatment ( Figure 2Cr is dispersed between diamond and copper, exhibiting a direct bond between them. Due to the poor wettability and significant differences in physical properties between diamond and copper, this direct bond interface severely hinders heat conduction, resulting in a low overall thermal conductivity of the material. However, after electrical pulse treatment ( Figure 3 Cr is significantly enriched between diamond and copper, forming a clear banded interface layer that effectively separates the diamond and copper. This Cr banded layer can significantly improve the wettability between diamond and copper, thereby constructing an efficient heat conduction path, effectively improving the interfacial heat conduction efficiency, and ultimately significantly improving the thermal conductivity of the material. Example 2
[0031] A highly efficient method for preparing diamond / copper composite materials is provided, comprising the following steps: S1: Raw material preparation: Select MBD8 type diamond particles with a particle size of 200μm, spherical chromium powder with a particle size of 10μm, and spherical copper powder with a particle size of 53μm. First, ultrasonically clean the diamond particles with deionized water for 30 min to remove water-soluble impurities adsorbed on the surface. Then, ultrasonically clean them with acetone for 10 min to remove organic matter on the surface. Further, ultrasonically clean them with anhydrous ethanol solution for 30 min to remove excess acetone solution. Further still, surface activation is performed by soaking in dilute nitric acid for 30 min. Subsequently, acidic dirt on the surface of the diamond particles is neutralized with sodium hydroxide solution. Finally, ultrasonically clean them multiple times with deionized water to remove excess impurities.
[0032] S2. Chromium plating on diamond surface: Chromium plating is performed on the cleaned diamond surface using a salt bath plating method. Diamond particles and chromium powder are mixed evenly at a molar ratio of 10:1 and placed in an alumina crucible. A layer of mixed salt (NaCl:KCl=1:1) is then placed on the surface. The crucible is placed in an atmosphere tube furnace and heated to 850 ℃ under Ar atmosphere protection for 60 min. The furnace is then cooled, washed with distilled water, and dried to obtain diamond particles with a coating.
[0033] S3. DC-assisted hot pressing sintering: Salt bath-plated diamond particles and copper powder are mixed at a volume ratio of 3:7, and then rapidly hot-pressed and sintered at a temperature of 900 ℃, a pressure of 80 MPa, and a holding time of 20 min.
[0034] S4. Electrical Pulse Treatment: The sintered diamond / copper composite material is subjected to electrical pulse treatment. The process parameters are: voltage 50 V, frequency 450 Hz, pulse time 2 min, duty cycle 97%, and current density 36.7 A / cm². 2 .
[0035] S5. After electrical pulse treatment, the diamond / copper composite material is cleaned by ultrasonic cleaning in anhydrous ethanol for 30 minutes to remove surface impurities. The material is then removed and dried to obtain a high-performance diamond / copper composite material. Example 3
[0036] A highly efficient method for preparing diamond / copper composite materials is provided, comprising the following steps: S1: Raw material preparation: Select MBD8 type diamond particles with a particle size of 200μm, spherical chromium powder with a particle size of 10μm, and spherical copper powder with a particle size of 30μm. First, ultrasonically clean the diamond particles with deionized water for 15 min to remove water-soluble impurities adsorbed on the surface. Then, ultrasonically clean them with acetone for 30 min to remove organic matter on the surface. Further, ultrasonically clean them with anhydrous ethanol solution for 15 min to remove excess acetone solution. Further still, surface activation is performed by soaking in dilute nitric acid for 30 min. Subsequently, acidic dirt on the surface of the diamond particles is neutralized with sodium hydroxide solution. Finally, ultrasonically clean them multiple times with deionized water to remove excess impurities.
[0037] S2. Chromium plating on diamond surface: Chromium plating is performed on the cleaned diamond surface using a salt bath plating method. Diamond particles and chromium powder are mixed evenly at a molar ratio of 10:1 and placed in an alumina crucible. A layer of mixed salt (NaCl:KCl=1:1) is then placed on the surface. The crucible is placed in an atmosphere tube furnace and heated to 900 ℃ under Ar atmosphere protection for 30 min. The furnace is then cooled, washed with distilled water, and dried to obtain diamond particles with a coating.
[0038] S3. DC-assisted hot pressing sintering: Salt bath-plated diamond particles and copper powder are mixed at a volume ratio of 3:7, and then rapidly hot-pressed and sintered at a temperature of 950 ℃, a pressure of 70 MPa, and a holding time of 10 min.
[0039] S4. Electrical Pulse Treatment: The sintered diamond / copper composite material is subjected to electrical pulse treatment. The process parameters are: voltage 60 V, frequency 400 Hz, pulse time 3 min, duty cycle 98%, and current density 30 A / cm². 2 .
[0040] S5. After electrical pulse treatment, the diamond / copper composite material is cleaned by ultrasonic cleaning in anhydrous ethanol for 30 minutes to remove surface impurities. The material is then removed and dried to obtain a high-performance diamond / copper composite material.
[0041] Comparative Example 1 This comparative example is basically the same as Example 1, except that the electrical pulse processing in step S4 is not performed.
[0042] Performance and organization testing: The thermal conductivity, coefficient of thermal expansion and density of the diamond / copper composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested before and after the electric pulse using the laser flash method, the push rod method and the mass-volume method, respectively. The test results of the thermophysical properties of the diamond / copper composite materials are shown in Table 1.
[0043] Table 1 Thermophysical properties of diamond / copper composites As shown in Table 1, after electrical pulse treatment, the thermal conductivity, coefficient of thermal expansion and density of Example 1 were improved compared with those of Comparative Example 1, indicating that electrical pulse post-treatment has a universal improvement on interfacial thermal conduction efficiency.
[0044] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A highly efficient preparation method for diamond / copper composite materials, characterized in that, The preparation method includes: S1. Cleaning and surface activation pretreatment of diamond particles; S2. Chromium plating is performed on the pretreated diamond surface using a salt bath plating method to obtain diamond particles containing a chromium plating layer. S3. The diamond particles containing the chromium plating layer are mixed with copper powder and subjected to DC-assisted hot pressing sintering to obtain a diamond / copper composite sintered body. S4. The diamond / copper composite sintered body is subjected to electrical pulse treatment, and after cleaning and drying, the diamond / copper composite material is obtained.
2. The efficient preparation method of diamond / copper composite material according to claim 1, characterized in that, In step S1, during the pretreatment process, the surface is ultrasonically cleaned with deionized water, acetone and anhydrous ethanol for 10-30 minutes respectively, then soaked in dilute nitric acid for 30 minutes for surface activation, neutralized with sodium hydroxide solution to neutralize the acidic dirt on the surface, and then ultrasonically cleaned with deionized water.
3. The efficient preparation method of diamond / copper composite material according to claim 1, characterized in that, In step S2, during the salt bath plating process, the molar ratio of diamond particles to chromium powder is 10:1, a mixed salt of NaCl:KCl of 1:1 is used, the plating temperature is 800~900℃, the holding time is 30~90 min, and the process is carried out under argon atmosphere protection.
4. The efficient preparation method of diamond / copper composite material according to claim 1, characterized in that, In step S3, the volume ratio of the diamond particles to the copper powder is 3:
7.
5. The efficient preparation method of diamond / copper composite material according to claim 1, characterized in that, In step S3, the DC-assisted heating sintering temperature is 800~950℃, the pressure is 70~90 MPa, and the holding time is 10~30 min.
6. The efficient preparation method of diamond / copper composite material according to claim 1, characterized in that, In step S4, the electrical pulse processing parameters are: voltage 40~60 V, frequency 400~500 Hz, and pulse time 1~3 min.
7. The efficient preparation method of diamond / copper composite material according to claim 6, characterized in that, The duty cycle of the electrical pulse processing is 95%~98%, and the current density is 30~40 A / cm². 2 .
8. The efficient preparation method of diamond / copper composite material according to claim 1, characterized in that, The diamond particles are MBD8 type diamond particles with a particle size of 200μm; the chromium powder is spherical chromium powder with a particle size of 10μm; and the copper powder is spherical copper powder with a particle size of 15~53μm.
9. The efficient preparation method of diamond / copper composite material according to claim 1, characterized in that, During the cleaning and drying process, the sample is ultrasonically cleaned in anhydrous ethanol for 30 minutes, then removed and dried.